Prevalence of HIV infection, Syphilis and hepatitis in men with STI symptoms - Miranda, Angélica E; Carvalho, Marcelo F; Lara, Luciana TR; Moherdaui, Fabio; Barreira, Draurio; Grupo de Estudo de DST/Aids – Instituto Adolfo LutzInstituto Adolfo Lutz (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: Access of and monitoring of prevalence data are important components for epidemiological surveillance of STD, by trends analysis,they can be useful for prevention and assistance strategies of health.Objectives: estimate seroprevalence of HIV infection, syphilis, and hepatitis Band C virus among male population with STI symptoms attending Health clinics. Methods: sentinel study was performed in 28 sites in 2003. Theused methodology was anonym, not associated blind. Samples were collected during 16 weeks, among male attendees from 15 to 49 years old. Thesamples were tested for determining antibody to HIV, syphilis, hepatitis C (HCV), and for the detection of surface antigen of hepatitis B. Results: itwas collected and tested 5,408 samples among men with symptoms of other STI. Mean age was 31.0 (SD 9.8) years old. Prevalence rates were: 3.8%(CI 95% 3.2-4.2) for HIV infection, 12.9% (CI 95% 11.9-13.7) for syphilis, 9.6% (CI 95% 7.8-11.2) for HBV infection and 2.7% (CI 95% 1.9-3.5) ofHCV infection. Conclusion: the access and monitoring of these data, that showed high prevalence of infections, are important skills forHIV/AIDS/STI epidemiological surveillance actions.